Situating the evidence for impact of outreach strategies: A systematic review for improving access to higher education. (1st April 2020) - Heaslip, Vanessa; Hutchings, Maggie; Collins, Bethan; Crowley, Emma; Eccles, Sue; Hunt, Clive; Tooth, Rae; Wardrop, Alex
Efforts to widen participation into higher education (HE) are having an impact with increasing numbers of diverse students accessing HE. Outreach is a key strategy within widening participation (WP), yet there has been little peer reviewed, published evidence regarding how outreach is identified, situated and understood. This paper addresses this gap, presenting a systematic review of published research examining how the impact of WP outreach is identified and understood in UK research. The Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) checklist was used to frame the review and empirical studies focusing upon outreach (2005 – 15) were included. Papers excluded were focused on international, part-time students or those not focused upon WP outreach. Twenty-six papers were identified for inclusion and these were analysed thematically. The analysis identified themes of person-centred impact, raising aspirations, and social capital, addressing 'how and why' questions rather than the 'what works' question judged by the impact of outreach on student numbers. Doing so can enable improvements in the design of outreach activities addressing individual experiences alongside structural barriers. Ultimately, this analysis suggests there is insufficient systematic evidence regarding the impact of outreach on the underlying structural factors shaping access to higher education.